Is commitment intrinsic to poetry? - El-Amri, Ali (Eddissi Languages Journal, 2026)
It remains true that the question of commitment arises at every moment throughout successive generations, but it is much more characteristic when it typically involves diverse intellectuals. In this respect, poetry stands out as a field of inquiry, even a favorite, in this area. Throughout history, it has undergone an evolving and multifaceted path, from pure lyricism and aestheticism to deliberately engaged poetry, finally culminating in the modern conception that offers a meditative and reconfigurative aspect.